Renewing with Growth - World Bank (Washington, DC: World Bank, 2021)
Latin America and the Caribbean suffered the largest death toll from Covid‐19 across developing regions and the sharpest decline in economic activity. With fewer school days and lower employment rates, with higher public debt and more firms under stress, the effects could be long‐lasting. The crisis also triggered large‐scale economic restructuring, with productivity higher in the expanding than in the contracting sectors. Accelerated digitization could instill dynamism in finance, trade and labor markets, but it may amplify inequality within and across the countries in the region. Technology could transform the energy sector as well. Latin America and the Caribbean has the cleanest and potentially cheapest electricity generation matrix of all developing regions. But its electricity is the most expensive, due mainly to inefficiencies. Distributed generation within countries and electricity trade across countries, could make energy greener and cheaper, provided that the pricing is right.